Augmented superior rectus transposition surgery for vertical strabismus in moebius syndrome - Mehta, Raman; Suma, Ganesh; Gupta, Reena Reena (Nepalese Journal of Ophthalmology, 2017)
Introduction: Moebius syndrome is a rare disease characterized by unilateral or bilateral congenital nonprogressive facial nerve palsy along with limitation of ocular abductions. Vertical Rectus Transpositions with posterior fixation suture is known to correct abduction deficiencies in case of Moebius syndrome. Traditionally both superior and inferior rectus transposition are done to prevent any post operative vertical imbalance. The purpose of reporting this case is to evaluate superior rectus transposition augmented with posterior fixation suture along with bilateral recession of medial rectus as a useful and safe alternative for treating large esotropia and abduction limitation with a significant vertical deviation in patients of Moebius syndrome. Case: We report a rare case of a seven year old male child with large esotropia and with limited ocular abductions along with a significant vertical deviation which is not common in classic Moebius syndrome. We performed a superior rectus transposition in the eye with vertical deviation along with bimedial recession and our post operative results indicated a significant correction in the horizontal as well as vertical deviation along with an improvement in head posture. Conclusion: We advocate a superior rectus transposition surgery in cases of moebius syndrom whenever there is a significant vertical deviation.